Synovial sarcoma of the head and neck: A review of reported cases on the clinical characteristics and treatment methods - Quan, Hongzhi; Sreekissoon, Senjeet; Wang, Yan (Frontiers in Cell and Developmental Biology, 2023)
Synovial sarcoma (SS) is a high-grade soft-tissue sarcoma that occurs predominantly in older children and young adults in their third decades. It is usually very challenging to diagnose and treat SS in the head and neck region. The purpose of this review is to investigate the clinical manifestations and different treatment methods in the management of primary synovial sarcoma of the head and neck. HNSS has an aggressive nature and poor prognosis. Surgical resection, radiotherapy, and chemotherapy are the primary treatment methods. Typically surgical resection with negative margins remains the foundation of therapy, which is not very easily achieved in the head and neck due to its complex anatomical structure and the presence of many blood vessels and nerves. However, SS has a high recurrence rate, so aggressive management and close follow-up are warranted for the optimal outcome.